2017
DOI: 10.1177/1947603517693045
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Defect Treatment Using High-Density Autologous Chondrocyte Implantation

Abstract: HD-ACI is a safe and effective technique for the treatment of cartilage defects, improving clinical and subjective perception of knee functionality. These preliminary results encourage future studies comparing this technique with traditional ACI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
5
31
0
Order By: Relevance
“…To solve these abnormalities, surgery by means of autologous chondrocyte transplantation with the techniques of ICA or ICAM are currently available. Even though the newly generated extracellular matrix after autologous chondrocyte transplantation is not the same as the native tissue generated it is still better than that the reparation of tissue (3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To solve these abnormalities, surgery by means of autologous chondrocyte transplantation with the techniques of ICA or ICAM are currently available. Even though the newly generated extracellular matrix after autologous chondrocyte transplantation is not the same as the native tissue generated it is still better than that the reparation of tissue (3).…”
Section: Discussionmentioning
confidence: 97%
“…The only way to restore the damaged cartilage is by surgery, which is often combined with autologous chondrocyte transplantation. Basically, a sample of healthy cartilage is taken and cells are multiplied, these cells are then implanted in the damaged cartilage after removing the injured area (3).…”
Section: Introductionmentioning
confidence: 99%
“…Cartilaginous tissue has no blood vessels or nerves, and is composed of 5% chondrocytes and 95% mesochondrium; thus, it has a poor self-repairing and regenerative capacity (12). Regenerative medicine has become a focal point, allowing regenerating of defective cartilaginous tissues using autologous chondrocytes (13)(14)(15). However, the application of chondrocytes in repair strategies has a number of limitations, including the limited availability of adult chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several studies have shown success with a variety of surgical techniques in a variety of patient populations. [5][6][7][8][9][10][11] There are limited randomized trials, however, to allow for effective comparison of the techniques that are most effective in treating isolated cartilage defects of the knee, specifically in adults. 12 Furthermore, secondary to the limitations of available high-level studies, the incidence of procedures performed has not been well described, especially with regard to indications.…”
mentioning
confidence: 99%
“…Thus, there continues to be debate regarding best practices, and practice trends continue to change as surgeons seek to improve current treatments with advancing techniques and refined indications. 10,[16][17][18][19] Despite questions regarding best practices and indications, McCormick et al 20 noted a 5% annual increase in the number of cartilage surgical procedures between 2004 and 2011.…”
mentioning
confidence: 99%